ANALISIS DESAIN PRODUK TERHADAP VOLUME PENJUALAN PADA MEUBEL SUWITO - Gustini, Sri (Jurnal Manajemen, 2019)
This study was to determine the impact of product design on the Suwito Sekayu Furniture on the sales volume of Musi Banyuasin Regency. This research was conducted at the Suwito Sekayu Furniture Musi Banyuasin District in 2015 with a sample of 83 respondents using Slovin. Data collection techniques using questionnaires, interviews and documentation. Data analysis uses quantitative analysis. The analysis shows that product design is part of marketing activities related to the steps used by companies in marketing a set of product lines offered to buyers. Product design relates to the concept of product life that serves to help explain the reasons for how important the implementation of product design in supporting company activities such as characteristics, performance, quality of conformity, durability, durability, reliability, ease of repair and models (Style).The impact of implementing product design is that it can increase profit changes, in other words it can increase a company's sales volume. Based on the description above can be seen product design with very close sales volume. By implementing a suitable product design in the face of a changing environment (both external and internal environment), the company will be able to overcome all kinds of obstacles or obstacles faced. In addition, the company will get a profitable product sales volume due to adjustments made company in accordance with the wishes of consumers or customers. This will increase the number of customers or consumers so that the profit or profit of the company will rise and the level of company's sales volume will increase.